Law Analysis Againt Calculatory and Children’s Crimension Under Age of Decision No. 19/Pid.sus/2016/PN.Slw - Sonya Airini Batubara*; Hendrianto Hendrianto; Ridho Nanda Wahyudi; Satizaro Harefa (Universitas Syiah Kuala, 2023)
Abuse is a crime against decency. Where the obscene act not only occurs in adults but also occurs in minors. The perpetrator of the crime of sexual abuse against minors can be committed by someone both against women and men. Sexual abuse or abuse of children is not only regulated in the Criminal Code but also regulated in more specifically regulated in Law No. 35 of 2014 on Child Protection in Articles 81 and 82 which states that: the punishment for perpetrators of sexual crimes against children is at least 5 years and a maximum of 15 years in prison and a minimum fine of Rp. 5,000,000,000.00 (five billion rupiah, While other punishments according to the Criminal Code articles 287 and 292 mention that the sentence period against the perpetrator of child abuse is a maximum of 9 years (article 287) and a maximum of 5 years (article 292). From the background and general review of the criminal acts of abuse and violence against minors, then the formula of the problem is how to account for criminal abuse and violence against minors based on the verdict No.19 / Pid.sus / 2016 PN.Slw and what about the legal protection of victims of criminal acts of abuse and violence against minors. In answering the formulation of the problem, then this study uses normative juridical research methods.